An Early North-Western Karaim Bible Translation from 1720. Part 1. The Torah - Németh, Michał (Karaite Archives, 2014)
In this article an early Bible translation into north-western Karaim is described. The manuscript, written in Hebrew script (in its Karaim semi-cursive variant), dates back to 1720, which makes it the oldest western Karaim Bible translation to be hitherto critically analysed. The manuscript was copied in Kukizów by Simcha ben Chananiel (died in the 1720s). The language of the manuscript reveals archaic features, among others, consonant harmony in the process of emerging.